Globalization of Health: Positive or Negative? (Anthropological Perspective) - Tajuddin, Fatjri Nur (European Journal of Social Science Education and Research, 2024)
This article examines the consequences of globalization on the health sector, how people see these conditions and how globalization is rejected or perhaps easily accepted as an effort in improving life. The majority of the world’s population in poor and developing countries do not have access to essential health services, let alone medicines. As a product of globalization, in the health sector, the conditions with humanitarian aspects as one of the indicators of the quality of human resources have been distorted and become a tempting element of economic commodities. In the era of globalization, international relations are getting closer. This problem is often known as global conditions. Global relations certainly have an impact on social life. These impacts bring changes in people’s behavior in various aspects of life. In the economic, political, social, cultural and security fields, this global impact not only affects large urban communities but also occurs in the rural communities. Along with this, the explanation in this article will be presented from an anthropological perspective.